2013
DOI: 10.1007/s11046-013-9630-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rolling Circle Amplification to Rapidly Identify Species of Cladophialophora Potentially Causing Human Infection

Abstract: The genus Cladophialophora comprises etiologic agents of disease in immunocompetent patients, ranging from mild cutaneous colonization to cerebral encephalitis, in addition to saprobic species. Due to the high degree of phenotypic similarity between closely related species of the genus, identification problems are imminent. In the present study, we described rapid and sensitive rolling circle amplification (RCA) method based on species-specific padlock probes targeted for the internal transcribed spacer region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The RCA padlock probe (FPgP) in the present study demonstrated greater sensitivity than previously reported probes developed for Fonsecaea species [13,15]. Given the specificity of the RCA padlock probes, RCA was judged to be suitable for Fonsecaea detection and species differentiation without sequencing in a wide range of biological samples.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The RCA padlock probe (FPgP) in the present study demonstrated greater sensitivity than previously reported probes developed for Fonsecaea species [13,15]. Given the specificity of the RCA padlock probes, RCA was judged to be suitable for Fonsecaea detection and species differentiation without sequencing in a wide range of biological samples.…”
Section: Discussionmentioning
confidence: 74%
“…In general, applicability of RCA padlock probe can range from bioprospecting, biotechnological potential [37], and biosensing [38] to diagnostic of viral [39] and bacterial [40] infections. Besides, some studies have already distinguished several CBM agents of the genus F. pedrosoi, F. nubica [10], and C. carrionii [13] and associated CBM species such as Exophiala [11,12] and Cyphellophora [43]. Several studies have reported the application of the RCA padlock probe to detect species-specific fungal diseases with great public impact, e.g., in opportunistic infections caused by species of Candida [16], Aspergillus [16], and Cryptococcus [7,41]; agents associated with systemic infections such as Histoplasma [18], Fusarium [42] and Talaromyces marneffei [15]; and dermatophytoses caused by species of the genus Trichophyton [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 RCA, a technique based on the rolling replication of short, single-stranded DNA circles by DNA polymerases under isothermal conditions, has been shown to be rapid, cost-effective and specific for molecular identification of human-and plant-pathogenic fungi, [15][16][17][18][19] including black yeasts and their relatives. [20][21][22][23] Kong et al 16 developed a rapid (2 h) and specific RCA-based single-nucleotide polymorphism detection assay for identification of clinically important Trichophyton species.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…RCA, a technique based on the rolling replication of short, single‐stranded DNA circles by DNA polymerases under isothermal conditions, has been shown to be rapid, cost‐effective and specific for molecular identification of human‐ and plant‐pathogenic fungi, including black yeasts and their relatives . Kong et al .…”
mentioning
confidence: 99%